Stereodivergent Transformation of Azepino[3, 4, 5‐cd]indoles En Route to Nature‐Inspired Scaffolds. Issue 9 (9th February 2023) - Srikanth, Gourishetty; Ravi, Anil; Sebastian, Anusha; Joseph, Jobi; Khanfar, Monther A.; El‐Gamal, Mohammed I.; Al‐Qawasmeh, Raed A.; Abu‐Yousef, Imad A.; Majdalawieh, Amin F.; Al‐Tel, Taleb H.
Abstract: Azepino[3, 4, 5‐ cd ]indole derivatives represent the core scaffold of important natural products and biologically relevant compounds. Therefore, the establishment of step‐ and atom‐economic strategies to access this class of compounds is of paramount importance. To this end, complexity‐to‐diversity (CtD) strategy has become one of the most important tools that transforms complex molecules into diverse skeleta. However, many of the reactions that could be employed in CtD are restricted by the functional handles exist in these molecules. This limits the achievement of the desired skeletal diversity. Herein, an efficient and step‐economic strategy to access a diverse collection of azepino‐[3, 4, 5‐ cd ]indole architectures through a cascade that combines Pictet‐Spengler with Michael addition, is described. This was achieved by reacting cyclohexadienone acetaldehydes 2 a –2 d with indolyl‐4‐ethyl amine 1 . Employing a CtD strategy on the developed azepino‐[3, 4, 5‐ cd ]indoles, a rapid rearrangement reaction that provided a modular, chemo‐ and diastereoselective access to diverse collection of spiro azepinocarbazole nature‐inspired frameworks, was encountered. Abstract : An efficient and step‐economic strategy was established that enables a facile access to highly functionalized azepino[3, 4, 5‐ cd ]indole architectures through a cascade combining Pictet‐Spengler and Michael addition. Employing a late‐stage transformation strategy on the developed azepino‐[3, 4, 5‐ cd ]indoles, provided a modular, chemo‐ and diastereoselective access to diverse collection of nature‐inspired frameworks, namely spiro[azepino[2, 3, 4, 5‐def]carbazole‐5, 1′‐cyclohexan]‐2′‐ene systems.